2016
DOI: 10.1037/cou0000155
|View full text |Cite
|
Sign up to set email alerts
|

Are you in the mood? Therapist affect and psychotherapy process.

Abstract: Studies on therapist factors have mostly focused on therapist traits rather than states such as affect. Research related to therapist affect has often looked at therapist baseline well-being or therapist reactions, but not both. Fifteen therapists and 51 clients rated pre- and postsession affect, as well as postsession working alliance and session quality, for 1,172 sessions of individual psychotherapy at a community clinic. Therapists' affect became more positive when clients were initially positive and when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 71 publications
5
36
3
2
Order By: Relevance
“…Client involvement also significantly predicted a positive session evaluation as rated by both clients and therapists across different theoretical orientations ( Eugster and Wampold, 1996 ). Related research on session evaluation has mostly looked at the client’s, rather the therapist’s, perceptions of session quality and its association with outcomes ( Hill and Lambert, 2004 ; Chui et al, 2016 ). Although we were unable to locate studies with counseling or psychotherapy students focusing on our particular variables, it has been shown that higher levels of therapists’ negative mood before sessions associated with lower levels of therapist-rated helpfulness of their interventions and the quality of the sessions ( Hill et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Client involvement also significantly predicted a positive session evaluation as rated by both clients and therapists across different theoretical orientations ( Eugster and Wampold, 1996 ). Related research on session evaluation has mostly looked at the client’s, rather the therapist’s, perceptions of session quality and its association with outcomes ( Hill and Lambert, 2004 ; Chui et al, 2016 ). Although we were unable to locate studies with counseling or psychotherapy students focusing on our particular variables, it has been shown that higher levels of therapists’ negative mood before sessions associated with lower levels of therapist-rated helpfulness of their interventions and the quality of the sessions ( Hill et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, few studies investigated well-being and affect during therapy, i.e. as a precursor, and/or a consequence of therapeutic sessions in therapists and patients (10). We do not know of any in forensic populations.…”
Section: Well-being In Therapymentioning
confidence: 99%
“…These can be summed up into aspects of therapist competence and adherence to therapy techniques on the one hand and therapeutic alliance aspects on the other (e.g. Chui et al, 2016;Newman et al, 2010;Prasko et al, 2011;Roos and Werbart, 2013;Weck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In psychotherapy short interventions, each single session and not only a long-term treatment perspective holds importance (e.g. Chui et al, 2016;Milbrath et al, 1999). Short-term psychotherapies with 4-18 sessions have proven successful (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation